The Moderating Effect of Perceived Effectiveness of SMEs' Marketing Function on the Network Ties—Strategic Adaptiveness Relationship. (17th February 2016) - Nyuur, Richard Benon‐be‐isan; Brečić, Ružica; Simintiras, Antonis
Abstract : This study examines the critical role of perceived effectiveness of the Marketing function (MF) in small and medium‐sized enterprises (SMEs) in leveraging entrepreneurial network ties to improve strategic adaptiveness (SA). The study tests whether a MF perceived as effective by SMEs' managers/owners moderates the relationship between SMEs network ties and SA required for improved performance. Findings of a moderated regression analysis on a sample of 263 Croatian SMEs indicate that network ties contribute significantly to their SA, and that a MF perceived as effective only moderates the impact of customer and competitor ties on SMEs' SA. Research and practical implications are discussed.